KAJIAN AIR HUJAN MELALUI LUBANG RESAPAN BIOPORI (LRB) DI UIN SUNAN AMPEL SURABAYA - Martha, Luluk; Hakim, Abdul; Setyowati, Rr Diah Nugraheni (Al-Ard: Jurnal Teknik Lingkungan, 2018)
Lack of green open space (RTH) can lead to flooding and even catastrophic flooding in the event of high rainfall intensity that falls in urban areas. Sunan Ampel State Islamic University Surabaya (UINSA) is one of the educational facilities in Surabaya City which is located in the flood prone area of Jemur Wonosari, Wonocolo. One of the technologies used to overcome inundation and flooding and to increase groundwater reserves is the Biopori Infiltration Hole (LRB). UINSA as one of the education facilities in Surabaya City can apply LRB technology to absorb rainwater so that it can reduce runoff of wasted rainwater into ditches to drainage systems. This study aims to determine the amount of LRB that can be applied in UINSA and the percentage of LRB in reducing drainage load. The method used is quantitative descriptive by conducting field survey of open land area, ground infiltration field test, soil type laboratory test and using secondary data daily rainfall. The results of the study showed that the number of LRB that can be applied at UINSA is 741 pieces in open spaces covering an area of 1481.84 m2 with a reduction in drainage load of 42.83%. Keywords: rainwater, biopori infiltration hole, infiltration, drainage load reduction.